Prevalence of Internet Gaming Disorder in Medical Students: A Meta-Analysis - Chiang, Christine L. L.; Zhang, Melvyn W. B.; Ho, Roger C. M. (Frontiers in Psychiatry, 2022)
Introduction In the last decade, the technological advances have led to increased usage of the Internet. Internet-based games are now more readily available, and they are also more attractive and engageable for individuals.. Previous studies have established university students as vulnerable population with regards to IGD. Despite the unique stressors and demands of the course, there is little information about the pooled prevalence of IGD in medical students. Objectives The current meta-analysis aims to establish the pooled prevalence of IGD among medical students in different countries, and factors affecting the pooled prevalence. Methods A comprehensive search was conducted from 23 May 2021 to 30 May 2021. The following databases were searched: PubMed, PsychINFO, Cochrane CENTRAL, Google Scholar, Scopus, Web of Science, Embase, Science Direct. The search terminologies included permutations of the keywords for IGD and medical students. All statistical analysis was performed with the Comprehensive Meta-analysis Version 3.0 program based on random-effects model. Results 396 articles were identified from the search of the databases. The final data set consisted of 6 studies with a pooled cohort size of 2236 medical students. The pooled prevalence of IGD in each country is as follows: Egypt had the highest prevalence rate of 10.9% (95% CI: 7.3 – 16.1%), followed by Saudi Arabia (8.8, 95% CI: 5.7 – 13.2%), Indonesia (6.1, 95% CI: 0.7 – 37.5%) and India (3.8, 95% CI: 2.7 – 5.5%) (p < 0.005). Conclusions In conclusion, this meta-analysis reports that the pooled prevalence of IGD among medical students from different countries is 6.2%, which is around twice as high than that of the general population.